Phytosociological study on the weed communities in green sugarcane field reform using conservation tillage and oilseed crops in succession - Soares, M. B.B.; Bianco, S. [UNESP]; Finoto, E. L.; Bolonhezi, D.; Albuquerque, J. A.A. (ALOKI, 2017)
The objective of this study was to evaluate the weed community in green sugarcane field reform with three tillage managements and oilseed crops in succession. The experiment was conducted during the 2007/08 season on a sugarcane area harvested without prior burning in the last five cuts. Treatments were arranged in a split-plot design with four replications. Whole plots were conventional-till, minimum-till and no-till cropping systems and the subplots were fallow or crop rotation with peanut, soybean or sunflower. After 180 days of sugarcane harvest, weeds have been identified, the number of weeds.m-2 was counted and biomass of weeds above ground were taken. All data were subjected to analysis of variance using a split-plot model and the means were compared by Tukey’s test at 5% probability. The phytosociological indices were calculated. No-till system in the reform of green sugarcane significantly reduces the number and biomass of weeds. The use of soybean and peanuts in rotation with sugarcane in field reform was beneficial to controlling the weed population and suppressing weed species difficult to control as Cyperus rotundus and Commelina bengalensis.
Keywords: Arachis hypogaea; Glycine max; Helianthus annuus; Minimum tillage; No-till